Vernacular names of species of Opuntia (Cactaceae) in Moroccan Arabic: Mechanisms of phytonymic lexicon production in Arabic and Spanish - Joaquín Bustamante Costa (Anales del Jardín Botánico de Madrid, 2019)
The languages that extend outside their original floristic sphere develop, to denominate new species, some mechanisms that remain their validity in force when the languages stop their expansion and are stabilized: Spanish and Arabic have gone through a parallel process to create vernacular names of plants before an exotic species: Acquisition of a term also exotic, readaptation of a patrimonial term that acquires a new meaning, or the creation of an entirely new plant name. In the article we analize these mechanisms to denominate American species of the genus Opuntia Mill. in the Moroccan Arabic in parallel with the Spanish. Around sixteen Moroccan vernaculars was mentioned and a hypothesis is raised about the Spanish chumbera (prickly pear cactus) and its cognate oriental Arabic ṣubbāra/ṣubbayra.